Stateless Syrians in Turkey and Lebanon - Eren, Deniz Aşkın (Border Crossing, 2020)
Emigration began in Syria following the civil war has caused a break in the legal citizenship bonds of millions of Syrians with their country, especially for those settled in neighbouring countries. The open door policy implemented by Turkey and Lebanon and the two countries hosting of the majority of this migrated population have made registration and some services in these countries even more intricate. Generally, the Syrians but especially children born outside of Syria can only be recognised as Syrian practically but not officially. People in this group who can be identified as de facto stateless face the risk of not enjoying fundamental human rights if they are not enrolled in the countries where they moved. In this respect, both being stateless and unregistered in the receiving country cause these individuals to face double victimisation. In this context, the situation experienced in Turkey and Lebanon was examined within the framework of de facto statelessness concept with reference to culture, identity, and integration.